High-latitude Hirnantian (latest Ordovician) brachiopods from the Eusebio Ayala Formation of Paraguay, Paraná Basin - Benedetto, Juan Luis Arnaldo (2013)
Examination of newly collected brachiopods from the Eusebio Ayala Formation of Paraguay reveals the occurrence of Arenorthis paranaensis sp. nov., Plectothyrella? itacurubiensis sp. nov., Hindella sp. and Eostropheodonta conradii (Harrington). Associated graptolites of the N. persculptus Zone indicate that the age of the fossiliferous beds is Hirnantian. The overall generic composition of the fauna is similar to that of the atypical Hirnantia Fauna of the Bani Province. The record in Paraguay of Arenorthis, hitherto only known from North Africa, together with species of Plectothyrella? and Eostropheodonta different from those recorded in the Kosov Province, emphasizing the affinities between the Paraguayan fauna and the low-diversity African assemblages. Stratigraphic and faunal evidence indicates that biogeographical links between South America and Africa already existed by the end of the Ordovician when most of the intra-cratonic basins of Gondwana were flooded during the postglacial sea level rise.